2022
DOI: 10.3390/ijerph19063706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbon Emission Taxes on Environmental and Economic Systems

Abstract: Carbon dioxide is believed widely to be the major contributor to global warming. Policymakers worldwide are turning to tax policies in an effort to abate carbon emissions. China is the largest emitter of carbon emissions on our planet. The central government, as well as the local official, has introduced a series of environmental regulations, such as environmental protection tax and emissions trading system, to reduce carbon emissions and improve environmental quality. In the near future, the carbon emission t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Our results are confirmed by other studies (Dietz and Rosa, 1997;Ghazouani et al, 2020;Zioło et al, 2020;Adebayo et al, 2021;Andrew Mejia, 2021;D'Orazio and Dirks, 2022;Tu et al, 2022), in the sense that an increase in energy taxes and imports leads to a decrease in greenhouse gas emissions (GHG), while an increase in GDP has a negative effect on the quality of the environment. On the other hand, in the long run, the same cannot be said about population density and increasing exports, in the sense that an increase in them leads to a decrease in greenhouse gas emissions and not to an increase in them, as we would have expected.…”
Section: Pooled Mean Group-pmg Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are confirmed by other studies (Dietz and Rosa, 1997;Ghazouani et al, 2020;Zioło et al, 2020;Adebayo et al, 2021;Andrew Mejia, 2021;D'Orazio and Dirks, 2022;Tu et al, 2022), in the sense that an increase in energy taxes and imports leads to a decrease in greenhouse gas emissions (GHG), while an increase in GDP has a negative effect on the quality of the environment. On the other hand, in the long run, the same cannot be said about population density and increasing exports, in the sense that an increase in them leads to a decrease in greenhouse gas emissions and not to an increase in them, as we would have expected.…”
Section: Pooled Mean Group-pmg Modelssupporting
confidence: 91%
“…Thus, policy formulations should focus on removing barriers to the development of digital finance. Because global carbon is considered to be the main contributor to global warming, global policymakers are pursuing a series of fiscal policies to reduce carbon emissions (Tu et al, 2022). The largest carbon emitter on our planet is China, which is why the government has introduced a number of environmental regulations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also demonstrated that environmental taxes did not have a "double dividend" effect. Zhu et al (2020a) reported that a carbon tax negatively impacted the economy, with the potential to slow economic growth in particular (Tu et al, 2022). Combined, these findings underscore the uncertainty of whether environmental taxes can bring into full play the benefits of economic growth and technological innovation investment in China.…”
Section: Introductionmentioning
confidence: 98%
“…According to the traditional concept, enterprises have born the extra cost of carbon emissions, which is not conducive to the improvement of enterprise performance ( Shukla et al, 2008 ; Zhu et al, 2020a ). Carbon emission taxes is not helpful to economic growing ( Tu et al, 2022 ). So that they are reluctant to engage in carbon reduction activities.…”
Section: Introductionmentioning
confidence: 99%